Process of ontology construction for the development of an intelligent system for the organization and retrieval of knowledge in biodiversity – SISBIO - Rover, Aires José (2006)
This work describes the ontology construction process for the development of an Intelligent System for the Organization and Retrieval of Knowledge in Biodiversity – SISBIO. The system aims at the production of strategic information for the biofuel chain Two main methodologies are used for the construction of the ontologies: knowledge engineering and ontology engineering. The first one consists of extracting and organizing the biofuel specialists´ knowledge, and ontology engineering is used to represent the knowledge through indicative expressions and its relations, developing a semantic network of relationships.